Pengaruh Dukungan Sosial Terhadap Kualitas Hidup Orang dengan HIV/AID Selama Masa Pandemi Covid-19 - Firman Firman; Nur Mukarromah; Ira Purnamasari; M Luthfi Adillah; Abigael Grace Prasetiani (PROFESSIONAL HEALTH JOURNAL, 2023)
Background: HIV is a disease that has a very broad impact on a person's life, one of the most common problems experienced is the low quality of life. The aim of this study was to determine the effect of social support on quality of life among people living with HIV/AIDS (PLWH) during pandemic. Method:This research was a cross sectional study, involved 133 respondents that took part in the survey. The social support was measured by (MSPSS), while the quality of life was measured by (WHOQoL-HIV-BREF). Results: The social support effected on quality of life with (p = 0.000 < = 0.05). Multiple logistic regression analysis showed that sosial support was the dominant variable that affected the quality of life in people living with HIV/AIDS with OR=22,413. Discussion: From this study that social support played an important role in a person's quality of life. Participation in the foundation made them showed an optimistic attitude and had a positive acceptance of the conditions they experience, so that they were relatively able to overcome difficulties. Conclusion: The social support effected on quality of life, and respondents who have high social support have a 22.413 times higher tendency to have a good quality of life compared to respondents who have moderate and low social support.